2019
DOI: 10.34014/2227-1848-2019-2-16-22
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in Elderly Out Patients

Abstract: The aim of the work is to study the daily practice of prescribing drugs at the outpatient stage of medical care and to analyze the data obtained based Beers 2012 criteria and STOPP / START version 1. Materials and Methods. The authors analyzed drug prescriptions for 150 outpatients, who were over 65 years old. Results. Cardiovascular diseases, diseases of the osteo-articular system and type 2 diabetes mellitus prevailed in the morbidity structure of patients. Oncological diseases, thyroid diseases, bronchial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Our results is greater than the average prevalence of PIP (43%), and 2 times greater than the average prevalence of PIP in European countries (22%) [11], [12]. Our results are comparable to the prevalence of PIP in Russia (30-45%) [14], [21], which is most likely due to a similar health care system. The results of the study show that 56% of elderly patients at the primary care level have a risk of a potential adverse medicine reaction that can lead to complications.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our results is greater than the average prevalence of PIP (43%), and 2 times greater than the average prevalence of PIP in European countries (22%) [11], [12]. Our results are comparable to the prevalence of PIP in Russia (30-45%) [14], [21], which is most likely due to a similar health care system. The results of the study show that 56% of elderly patients at the primary care level have a risk of a potential adverse medicine reaction that can lead to complications.…”
Section: Discussionsupporting
confidence: 51%
“…In the United States of America, a long population study revealed determined that about 80% of older people regularly took at least two medicines, and 36% took at least five medicines [22]. In Russia, according to one study at the primary care level, about 52% of elderly patients take 4 or more medicines [14], and according to another, 37% take 5 or more medicines [21], the level of polypharmacy in Kazakhstan is higher. The statistical relationship that we have identified between the number of medicines taken and the presence of PIP also indicates the importance of preventing polypharmacy in elderly patients to prevent the occurrence of ADR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation